Efficacy of dabrafenib/trametinib in pancreatic ductal adenocarcinoma with BRAF NVTAP deletion: A case report - Shin, Ji Eun; An, Ho Jung; Park, Hyung Soon; Kim, Hyunho; Shim, Byoung Yong (Frontiers in Oncology, 2022)
Researches have been actively conducted to identify actionable mutations and incorporate them into clinical practice in pancreatic ductal adenocarcinoma (PDAC), which is known to have poor prognosis with traditional cytotoxic chemotherapy. BRAF point mutation in V600E is commonly reported in KRAS wild type PDAC and targeting of BRAF V600E is already being applied in various carcinomas including PDAC. Accumulated evidence also shows that not only BRAF_V600E but also short in-frame deletion of BRAF has oncogenic function. Here, we report the patient with BRAF N486_P490 deletion was initiated on dabrafenib/trametinib, a BRAF inhibitor/MEK inhibitor respectively after cytotoxic chemotherapy failure, then presented with a partial response.